Pemungutan Retribusi Parkir Indomaret dan Alfamart Berdasarkan Peraturan Daerah Kota Malang - Saputro, Kresna Dwi; Anggraini, R.A Rini; Soetijono, Iwan Rachmad (University of Jember, 2015)
Collecting retribution is a policy from the regional government. The function of it is to improve the regional income where kinds of collecting retribution, one of them are parking retribution in Malang city, the parking retribution has been an amendment to regional law Malang city area number 3 of 2015. it is about public service retribution that is to improve regional income from the parking retribution. The amount of them is great because Malang is a big city. However, the real conditions do not match with the regional law, e.g it happens at some Indomaret or Alfamart minimarkets. The regional law states that at this minimarket, the customers must not pay for the parking retribution because the regional government has accepted a parking tax given by Indomaret or Alfamart's company. KEYWORDS: Parking Retribution, Regional Goverment, Indomaret and Alfamart.